Saberes da monitoria: uma análise a partir do curso de pedagogia da Universidade Federal da Paraíba - Medeiros, Liara das Graças Costa de (2018)
The present research aims to analyze the knowledges provided by the monitorship experience in the scope of training for teaching in higher education, specifically in the course of Pedagogy - Campus I of the UFPB. The participation of professors of Undergraduate Courses of the UFPB, in this Program, is effective from the elaboration, inscription and approval of Teaching Projects that articulate two or more curricular components in action plans. In the case of undergraduate students with an average of 7.0 or higher (seven), participation in this program is effective after enrollment and approval in a selective process of the curricular component. The research is centered in the activities analysis of the pedagogy course monitors engaged in teaching projects of the Departments of Pedagogical Enhancement (DHP) and Fundamentation of Education (DFE) of the Education Center (CE) of the UFPB. Understanding pedagogues as professionals who have teaching as a field of study and being this action of teaching and learning experienced in the monitorship process, main object of this study, we rely on the theoretical information of tardif (2012), Anastasiou (2006), Veiga (2012, 2006), Ramalho (2007), Gil (2017) to conceptualize the teaching knowledges, and more specifically, the knowledges of university professors. So that the monitorship is considered as an effective Teaching Initiation Program, the studies of Dias (2012) and Natário (2001) were used. From a methodological point of view, the approach to qualitative research is the one that applies to this study and followed the following steps: first we carried out a bibliographical survey and in an exploratory phase was carried out, a documentary research with the intention of analyzing the activities recorded in the final report by the monitors at the end of the monitorship process, based on what was defined in monitorship projects of the DHP and DFE; in a second moment, interviews were carried out with two professors, coordinators of the monitorship Projects of the Departments mentioned above, and with seven monitors, all of the Pedagogy course, with the intention of proceeding to the analysis of the monitorship lived in the Course of Pedagogy, from the perspectives of student monitors and of project coordinators professors. The data were processed through content analysis, as described by Bardin (1979). The analysis of this Program, in relation to the Pedagogy Course, was also able to provide a more concrete and expanded vision of the knowledge’s that should be contemplated in teaching and in the monitorship. The knowledge of monitoring refers to the pedagogical knowledge, which involves the dimensions of planning, execution and evaluation of teaching, knowledge of knowledge or academic, and also provides the knowledge of the experience of being a monitor. They also point out, in the specific case of the pedagogy course monitors, for the construction of teaching knowledges in higher education and in addition to higher education, establishing an interface with the professional and academic field in which they can act the pedagogues. Thus, the analysis of this Program, we intend to Thus, the analysis of this Program, we intend to contribute to the strengthening of the program in the UFPB itself, as well as to other researches that may analyze, deepen, develop and transform the knowledges of the monitoring applying them in other areas.